PENGEMBANGAN MEDIA BAJU ARITMATIKA TERHADAP KEMAMPUAN ARITMATIKA PADA ANAK USIA DINI - Ifa Aristia Sandra Ekayati; Nilda Lailatur Rokhmah (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2021)
This study aims to provide new innovations to facilitate the teaching and learning process in delivering counting 1-10 material. This makes it easier and increases student focus in recognizing the symbols of numbers 1-10. The research method used using the research model from Borg an Gall, the researcher managed to summarize the results of this research method, including The feasibility test of the media in the teaching and learning process, b. Improve children's ability to recognize simbols 1-10 The media for arithmetic clothes is expected to be a way out in solving the difficulties of early childhood recognizing numbers 1-10, the arithmetic clothing media presents color and enthusiasm for children to recognize numbers 1-10, so that children will focus more on following the learning process. Data were obtained through questionnaires and interviews. Participants in this study were 5 validators from PG PAUD study program lecturers, the results of the study of two validators with the sum of the scores, the media of arithmetic clothes on validator I got a score of skor 90,47 (No revision, valid ), and the validator II got a score of 85,45 (Not revised, valid).